2020
DOI: 10.1186/s13007-020-00589-2
|View full text |Cite
|
Sign up to set email alerts
|

Development of a system for efficient callus production, somatic embryogenesis and gene editing using CRISPR/Cas9 in Saffron (Crocus sativus L.)

Abstract: Background: Crocus sativus is a recalcitrant plant for genetic transformation and genetic improvement, largely due to difficulties in Agrobacterium mediated transformation and vegetative reproduction. Effective genome editing requires proficient callus production and an efficient method to deliver Cas9 and sgRNAs into the plant. Here, we demonstrate Agrobacterium-mediated transformation of saffron. Further, we developed a CRISPR-Cas9 based system in this plant, for efficient gene knockout or edits in future. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Approximately 81% of survival rate was reported in a similar study utilizing 0.1% (w/v) carbendazim, 0.2% (w/v) mancozeb followed by 50% (v/v) sodium hypochlorite and 1.6% (w/v) mercuric chloride in C. sativus (Yasmin and Nehvi 2014). The use of 0.1% mercuric chloride followed by 4% sodium hypochlorite resulted in 86% survival rate in C. sativus (Chib et al, 2020). Results showed that the development of disinfection protocols for wild crocus species is more challenging than C. sativus, maybe because of their recalcitrant nature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Approximately 81% of survival rate was reported in a similar study utilizing 0.1% (w/v) carbendazim, 0.2% (w/v) mancozeb followed by 50% (v/v) sodium hypochlorite and 1.6% (w/v) mercuric chloride in C. sativus (Yasmin and Nehvi 2014). The use of 0.1% mercuric chloride followed by 4% sodium hypochlorite resulted in 86% survival rate in C. sativus (Chib et al, 2020). Results showed that the development of disinfection protocols for wild crocus species is more challenging than C. sativus, maybe because of their recalcitrant nature.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that 0.25 mg/L 2,4-D þ 1 mg/L BAP showed the best results for callus initiation and callus growth in Crocus (Zeybek et al, 2012); while 4 mg/L NAA þ 4 mg/L TDZ was proved to successfully induce callus in five Crocus species (Verma et al, 2016). In another report, over 70% callus induction was achieved using MS medium containing 0.5 mg/L 2,4-D, 1 mg/L BAP and 1 mg/L IAA (Chib et al, 2020). It is also reported that higher levels of auxin relative to cytokinin had increased somatic embryogenesis in the Ajowan calli (Carum copticum L.) (Niazian et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the f3ha-f3hb mutant plants had visible changes, pale purplish-pink flower color, while the rest, including plants with a single-copy gene knockout, had purple-violet flowers that resembled wild-type petunia. Chib et al [ 128 ] established a CRISPR/Cas9-based system for future research advancements in saffron ( Crocus sativus L.). Zhang et al [ 129 ] presented evidence for redefining DPL’s role (DPL: THE R2R3-MYB transcription factor, which is connected to anthocyanin, has been linked to the regulation of corolla tube venation) in Petunia plants.…”
Section: Applications Of Crispr/cas9 System In Floriculturementioning
confidence: 99%
“…Crocus sativus L., also known as saffron, is the most precious spice in the world (Chib et al 2020). This species spreads from central Europe to western China (Harpke et al 2013).…”
Section: Introductionmentioning
confidence: 99%